Achievements and prospects of breeding researches on soybean (Glycine max) in India - BHATNAGAR, P S; KARMAKAR, P G (The Indian Journal of Agricultural Sciences, 2012)
In India 50 varieties of soybean [Glycine max(L.) Merr.] have been bred, for cultivation in the tropical agriculture of5 agro-climatic zones. Varietal improvement for genetic enhancement of yield, stability under vagaries of monsoon, good seed longevity, early maturity, resistance to pod shattering as well as against biotic and abiotic stresses have was thrust areas in domestic breeding of soybean. The major achievements were the development of varieties with high yield, pod-shattering resistance. early maturity improved seed longevity and resistance to yellow mosaic virus, e.g. varieties 'PK 472', 'JS 71-05', 'JS 335', 'PK 416'. 'Bragg', 'Pusa 16', 'NRC 2' and 'JS 80-21'. Various sources for seed longevity and resistance to pod shattering as well as important diseases and pests are being used in the domestic breeding programme to evolve varieties resistant to biotic and abiotic stresses. Hybridization of genetically divergent parents having high harvest index, high biomass yield,long seed-filling duration and good general combining ability can result in transgressive segregates for higher seed yield(3.5-4.0 tonnes/ha). Breeding of varieties with higher seed yield (2.5-Â·3.0 tonnes/ha) in early-maturing group (85 -105 days, depending on the agro-climatic zone), with improved resistance to pod shattering (up to 10 days after maturity), and good seed longevity (ability to retain seed viability of> 70% after 8-9 months of storage under ambient Condition), suitable for mechanical harvesting are the thrust areas of soybean breeding research for future. As chemical characters are of economic importance in soybean, researchers have identified lines having higher oil content (22-23%), low linolenic acid (25 g/kg) and absence of lipoxygenase isoenzymes or trypsin-inhibitor activity. Beany flavor in soybean is due to linolenic acid and lipoxygenase enzymes present in it at maturity. These lines can be used to incorporate the desirable qualities into improved Indian varieties of soybean.